The patient-rated elbow evaluation was successfully translated into the Arabic language - Abdelmegeed, Mohamed; Awad, Catherine; MacDermid, Joy; Kaddah, Mohamed; Fayaz, Nadia (Journal of hand therapy, 2023)
•The patient-rated elbow evaluation (PREE) was successfully translated into the Arabic language using published guidelines•An expert committee has reconciled some terminologies in the newly adapted Arabic version of the patient-rated elbow evaluation (PREE-AR)•The PREE-AR is valid and reliable to use in Arabic-speaking subjects with elbow pain.•The PREE-AR has comparable psychometric properties to the other versions.•The PREE is recommend it to be used with Arabic-speaking patients with elbow pathologies both in clinical and research settings.